Thriving on waves of change: Case study of an agile digital business in Singapore. Issue 2 (November 2020) - Teoh, SayYen; Chan, Calvin ML
Much has been written and said about the need to be agile for businesses to transform themselves and adapt in the dynamic digital economy. This case study traces the history of a Singaporean IT firm from its inception in 1993 to 2019. In particular, this case study illustrates how agility has enabled the company to grow from a start-up to be among the leading IT firms in Singapore albeit operating in the dynamic IT industry that has grown increasingly volatile with the emergence of disruptive digital technology and innovation. Apart from drawing insights on organizational agility and adaptation, this case study also provides illustration on the theme of entrepreneurship and leadership as manifested through the Founder and Chief Executive Officer.